2020
DOI: 10.1016/j.chest.2020.08.1936
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory Pharmacology of Ensifentrine

Abstract: PURPOSE: Ensifentrine, a trequinsin analog, is an investigational dual inhibitor of PDE3 and 4 designed to enhance bronchodilator and anti-inflammatory effects locally in the airways and minimize possible adverse systemic effects through direct delivery via inhalation. Ensifentrine has shown bronchodilatory effects in clinical studies in patients with COPD and asthma (Singh 2020, Bjermer 2019). Anti-inflammatory effects including a significant reduction in inflammatory cells (e.g. neutrophils) have been shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In enzyme activity assays of recombinant PDE3A, PDE3B, and PDE4B2, ensifentrine inhibited PDE activity with IC 50 values of 0.25, 0.29 and 290 nM, respectively. 26 The inhibitory activity of ensifentrine on PDE4 was aligned with the positive control rolipram (130 nM) 26 and with reported functional activity of ensifentrine on PDE4-mediated inhibition of TNFα production in lipopolysaccharide (LPS)-stimulated human monocytes (520 nM) and proliferation of human mononuclear cells stimulated with phytohemagglutinin (460 nM). 15 Ensifentrine has been shown to increase levels of cAMP in human neutrophils and CFBE41o-WT cells, demonstrating the ability of ensifentrine to inhibit PDE3 and PDE4 and produce expected effects in a cellular mechanistic assay.…”
Section: Non-clinical Datamentioning
confidence: 65%
“…In enzyme activity assays of recombinant PDE3A, PDE3B, and PDE4B2, ensifentrine inhibited PDE activity with IC 50 values of 0.25, 0.29 and 290 nM, respectively. 26 The inhibitory activity of ensifentrine on PDE4 was aligned with the positive control rolipram (130 nM) 26 and with reported functional activity of ensifentrine on PDE4-mediated inhibition of TNFα production in lipopolysaccharide (LPS)-stimulated human monocytes (520 nM) and proliferation of human mononuclear cells stimulated with phytohemagglutinin (460 nM). 15 Ensifentrine has been shown to increase levels of cAMP in human neutrophils and CFBE41o-WT cells, demonstrating the ability of ensifentrine to inhibit PDE3 and PDE4 and produce expected effects in a cellular mechanistic assay.…”
Section: Non-clinical Datamentioning
confidence: 65%
“…6 Multiple in-vitro and in-vivo studies have demonstrated dose-dependent bronchodilator, bronchoprotective and anti-inflammatory effects of ensifentrine. 15,16 Multiple clinical studies have demonstrated similar effects of this drug when tested on healthy individuals and patients with asthma or COPD. In 4-week, phase II clinical trials, nebulized drug given twice a day alone or in combination with other bronchodilators, showed sustained bronchodilation and improvement in FEV1, improvement in symptoms judged by questionnaires, improvement in residual volumes and COPD symptoms.…”
Section: Discussionmentioning
confidence: 98%
“… 6 Multiple in-vitro and in-vivo studies have demonstrated dose-dependent bronchodilator, bronchoprotective and anti-inflammatory effects of ensifentrine. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensifentrine is a novel PDE3/4 (phosphodiesterase 3 and 4) dual inhibitor, described as such because it potently inhibits each isolated recombinant enzyme ( 2 ) and shows functional activity in cellular and tissue assays consistent with PDE3 inhibitory effects (approximately 50% inhibition of contraction of tracheal preparations at a concentration of 100 nM) and PDE4 inhibitory effects (inhibition of TNFa production in human monocytes [half maximal inhibitory concentration (IC 50 ) = 520 nM] and proliferation of human mononuclear cells [IC 50 = 460 nM]) ( 2 , 3 ). Furthermore, in vivo pharmacology models with inhaled ensifentrine in guinea pigs also demonstrated that ensifentrine produced dose-dependent effects in animal models of lung inflammation at the same doses that produced bronchoprotective and smooth muscle effects ( 4 ). In healthy volunteers after lipopolysaccharide challenge, significant reductions in sputum inflammatory cells (e.g., neutrophils, macrophages, lymphocytes, and eosinophils) were observed after 6 days dosing with once-daily inhaled ensifentrine ( 5 ).…”
mentioning
confidence: 99%